24S‐hydroxycholesterol: cellular effects and variations in brain diseases - Sodero, Alejandro Omar (2020)
The adult brain exhibit a characteristic cholesterol homeostasis, with low synthesis rate and active catabolism. Brain cholesterol turnover is possible thanks to the action of the enzyme Cytochrome P450 46A1 (CYP46A1) or 24-cholesterol hydroxylase, that transforms cholesterol into 24S-hydroxycholesterol (24S-HC). But before crossing the blood-brain barrier (BBB), this oxysterol that is the most abundant in the brain can act locally, affecting the functioning of neurons, astrocytes, oligodendrocytes, and vascular cells. The first part of this review addresses different aspects of 24S-HC production and elimination from the brain. The second part concentrates in the effects of 24S-HC at the cellular level, describing how this oxysterol affects cell viability, amyloid beta production, neurotransmission, and transcriptional activity. Finally, the role of 24S-HC in Alzheimer, Huntington and Parkinson diseases, multiple sclerosis and amyotrophic lateral sclerosis, as well as the possibility of using this oxysterol as predictive and/or evolution biomarker in different brain disorders is discussed.